Varies Experience in Patients Referred for an Orthodontic Consultation - Kristian Tadić; Višnja Katić; Stjepan Špalj (University of Zagreb. School of Dental Medicine, 2018)
Objective of work: Caries represents a significant public health problem. Caries free dentition and good oral hygiene are prerequisites for inclusion into orthodontic treatment. The objective of this research was to assess oral health of the patients referred for an orthodontic assessment. Subjects and methods: In this cross sectional study, dental records of 351 patients aged 6-23 years (55% females), were referred to an orthodontist by general dentist during 2014 and 2015 in the Rijeka region, and the records were subsequently analyzed. Prevalence of caries, caries experience and active caries related to gender and dentition type were analyzed. Results: In subjects with the mixed dentition, who were referred to an orthodontist, caries prevalence was 68% in deciduous teeth, caries experience was 3.6, and active caries was present in 2.5 teeth; in permanent teeth in mixed dentition the values were 21%, 1.3 and 0.4., respectively. The values in subjects with permanent dentition were as follows: 40%, 4.2, and 1.1. Caries was more frequent in deciduous teeth, and there were more fillings in permanent teeth compared to deciduous teeth. There were no gender related differences. Conclusions: Oral health of children and adolescents referred to an orthodontic consultation is not satisfactory. General dentists frequently refer patients with caries to an orthodontic consultation. However, the presence of caries postpones inclusion into orthodontic treatment. It is important to begin raising general dentists' awareness of the need to refer to an orthodontist only those patients who have healthy dentition and good oral hygiene.